(untitled) (Research, Society and Development, 2020)
Introduction: The Intensive Care Unit (ICU) is one of the sectors of the hospital where patients are at critical stages. Due to the clinical situation of the patient and the period of stay in the unit, several injuries can occur to the patient, among them, the pressure injury, which is caused by the lack of oxygen and nutrients supply in the tissues. Objective: To evaluate the benefits of the applicability of the Braden Scale in patients in the Intensive Care Unit. Methodology: This is a qualitative research with a descriptive approach. It was performed in four ICUs of a philanthropic hospital in Teresina-PI. The research subjects were eight nurses of the sector. Data were collected from September to November 2017, through a semi-structured interview script. For the analysis of the data, the technique of Collective Subject Discourse was used. Results and Discussion: The data were organized into two thematic categories: Applicability of the Braden Scale to patients in the Intensive Care Unit and Benefits provided by the Braden Scale to inpatients. The applicability of the scale as a fundamental method for the prevention of Pressure Injury is evidenced. And as for the benefits, there are several as fewer expenses with special dressings and a shorter hospital stay. Conclusion: The applicability of the Braden Scale in the ICU context proved to be effective in the prevention of Pressure Injury. Its use of admission, multidisciplinary visit and patient evolution provide predictive measures of this aggravation. The benefits promoted by the use of the scale are mainly the prevention of Pressure Injury, the identification of patients at risk, the recognition of risk factors for the development of LPP and the subsidy to guide care practices.